The Demographic Effects of Colonialism: Forced Labor and Mortality in Java, 1834–1879 - de Zwart, Pim; Gallardo-Albarrán, Daniel; Rijpma, Auke (The Journal of economic history, 2022)
We investigate the demographic effects of forced labor under an extractive colonial regime: the Cultivation System in nineteenth-century Java. Our panel analyses show that labor demands are strongly positively associated with mortality rates, likely resulting from malnourishment and unhygienic conditions on plantations and the spread of infectious diseases. An instrumental variable approach, using international market prices for coffee and sugar for predicting labor demands, addresses potential endogeneity concerns. Our estimates suggest that without the abolition of the Cultivation System average overall mortality in Java would have been between 10 and 30 percent higher by the late 1870s.